2010
DOI: 10.1371/journal.ppat.1001177
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Evades Type I Interferon Antiviral Signaling by Inducing the Suppressor of Cytokine Signaling 1 (SOCS1)

Abstract: Human T cell leukemia virus type 1 (HTLV-1) is the etiologic agent of Adult T cell Leukemia (ATL) and the neurological disorder HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Although the majority of HTLV-1–infected individuals remain asymptomatic carriers (AC) during their lifetime, 2–5% will develop either ATL or HAM/TSP, but never both. To better understand the gene expression changes in HTLV-1-associated diseases, we examined the mRNA profiles of CD4+ T cells isolated from 7 ATL, 12 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 72 publications
(93 reference statements)
2
62
0
Order By: Relevance
“…However, other studies showed that Foxp3 expression in Tregs was stabilized by the cellular protein SOCS1 (60). The SOCS1 protein is upregulated by HTLV-1 infection, specifically, by Tax-1 (61,62). Previous observations suggested that ATL cells, which act phenotypically like Tregs, have high levels of expression of Foxp3 and maintain Tax expression (63).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies showed that Foxp3 expression in Tregs was stabilized by the cellular protein SOCS1 (60). The SOCS1 protein is upregulated by HTLV-1 infection, specifically, by Tax-1 (61,62). Previous observations suggested that ATL cells, which act phenotypically like Tregs, have high levels of expression of Foxp3 and maintain Tax expression (63).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism is not fully understood, Hishizawa et al have shown that dendritic cells isolated from HTLV-1-infected individuals have an impaired ability to secrete type 1 IFN (16). In addition, it has been reported that the cellular protein SOCS, which inhibits STAT1 phosphorylation, inhibits intracellular signal transduction downstream of the IFN receptor, IFNAR1/2, in both ex vivo CD4 ϩ cells from HTLV-1-infected individuals and in vitro in HTLV-1-infected cells (50)(51)(52). Moreover, in HTLV-1-infected cells in vitro, the level of phosphorylation of Tyk2 and STAT2, two key molecules in the activation cascade of the IFN pathway, is decreased (53).…”
Section: Discussionmentioning
confidence: 99%
“…+ T cells from HAM/TSP and asymptomatic carriers, and correlates with viral replication [58] . In particular, SOCS-1 inhibits IFN expression and IFN-stimulated gene expression [58] .…”
Section: Cd4mentioning
confidence: 99%
“…In particular, SOCS-1 inhibits IFN expression and IFN-stimulated gene expression [58] . SOCS adaptors are bound to cullin-2 and -5 through elongin C and elongin B proteins to constitute ubiquitin ligase complexes [59] .…”
Section: Cd4mentioning
confidence: 99%